Enhanced photocatalytic degradation of methylene blue by WO3/ZnWO4 composites synthesized by a combination of microwave-solvothermal method and incipient wetness procedure - Yanee Keereeta (2018)
© 2015 Elsevier B.V. ZnWO < inf > 4 < /inf > nanoparticles were successfully synthesized by microwave-solvothermal method. Subsequently, the incipient wetness procedure was used to load WO < inf > 3 < /inf > into ZnWO < inf > 4 < /inf > matrix and to form the WO < inf > 3 < /inf > /ZnWO < inf > 4 < /inf > composites with different morphologies. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), Raman spectrophotometry, and electron microscopy (EM) were used to characterize the phase, oxidation state, composites, and morphology. According to the Scherrer formula and the Brunauer-Emmett-Teller (BET) adsorption, average crystallite sizes of the nanoparticles are less than 30nm and 45nm, respectively, larger than the direct measurement by TEM. The 3.23eV direct energy gap (E < inf > g < /inf > ) and the 478nm emission wavelength of 3mol% WO < inf > 3 < /inf > /ZnWO < inf > 4 < /inf > composites were determined by UV-visible absorption and photoluminescence (PL) spectroscopy. The photocatalytic degradation of methylene blue (C < inf > 16 < /inf > H < inf > 18 < /inf > N < inf > 3 < /inf > SCl) was greatly enhanced by WO < inf > 3 < /inf > loading in ZnWO < inf > 4 < /inf > matrix to form WO < inf > 3 < /inf > /ZnWO < inf > 4 < /inf > composites. In this research, 3mol% WO < inf > 3 < /inf > -loaded ZnWO < inf > 4 < /inf > offered the best photodegradation performance of methylene blue at 36.21% within 300min and 55.54% within 480min under UV light irradiation.